Analysis of Tax Impact on Employee Retention in the Hospitality Industry - Darmono Darmono; Su’un, Muhammad; Bayu, Muhammad; Mursyidin , Mursyidin; Sappewali, Badriah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This qualitative research investigates the intricate relationship between taxation policies and employee retention within the hospitality industry. Employing a systematic literature review, the study examines the impact of tax incentives and management strategies on employee satisfaction and organizational practices. Through rigorous data collection and thematic analysis, key findings emerge, revealing the nuanced dynamics at play. The research underscores the significance of tax incentives in fostering employee loyalty and commitment, albeit contingent upon organizational culture, industry-specific factors, and perceived fairness. Additionally, it highlights the challenges posed by compliance costs and the ethical dilemmas associated with aggressive tax planning. The study contributes to a deeper understanding of the complex interplay between taxation policies, organizational responses, and employee outcomes, offering insights for both academia and industry practitioners.